ANALISIS FAKTOR RISIKO KEJADIAN TUBERKULOSIS PARU - Hasriani; La Rangki (Jurnal Kesehatan Al-Irsyad, 2020)
The medical record data at the Napabalano Health Center for pulmonary TB in 2016 from January to December was 315 suspected cases, whereas in 2017 the January-December period suspected 261 cases of pulmonary TB were suspected. This study aims to analyze the risk factors for TB pulmonary disease in Napabalano District, Muna Regency. The research design is the Case Control Study. The study population was all suspected pulmonary TB in Napabalano Subdistrict, Muna Regency, from January to December 2017 totaling 261 cases with the number of sample cases 57 and controls 57 taken with Simple Random Sampling technique. The results showed that occupancy density was a risk factor for pulmonary TB incidence, respondents who were at home with dense occupancy ie> 1 person per 10 m2 at risk of suffering pulmonary TB by 6 times compared to respondents who were at home not dense at <1 person per 10 m2 . Nutritional status is a risk factor for pulmonary TB incidence, respondents with poor nutritional status <18 IMT risk at risk of developing pulmonary TB 33 times compared to respondents with normal nutritional status BMI value 18-24. There is that there are risk factors for occupancy density, nutritional status, towards the incidence of pulmonary TB.